Extracellular Adenosine Triphosphate Binding to P2Y1 Receptors Prevents Glutamate-Induced Excitotoxicity: Involvement of Erk1/2 Signaling Pathway to Suppress Autophagy - Xiong, Yiping; Zhou, Duanyang; Zheng, Kai; Bi, Wenchuan; Dong, Yun (Frontiers in Neuroscience, 2022)
Glutamate-induced neuroexcitotoxicity could be related to the pathophysiology of some neurodegenerative diseases including Parkinson’s disease and Alzheimer’s disease. Extracellular ATP exerts a wide variety of functions, such as attenuating Aβ-mediated toxicity, inhibiting NMDA receptor subunit combinations, and aggravating ischemic brain injury. However, the effect of extracellular ATP on glutamate-induced neuroexcitotoxicity remains largely unknown. Herein, we showed that extracellular ATP prevented the glutamate-induced excitotoxicity via binding to its P2Y1 receptors. We found that excessive glutamate triggered cellular ROS overproduction and mitochondrial membrane potential damage, which were significantly attenuated by extracellular ATP. Besides, glutamate activated autophagy, as illustrated by the increased protein level of autophagic marker LC3II and decreased level of p62, and glutamate-induced neuroexcitotoxicity could be completely abolished by autophagy inhibitor chloroquine. In addition, we revealed that extracellular ATP activated Erk1/2 signaling to suppress autophagy and to exert its neuroprotective effects, which was further reduced by autophagy agonist rapamycin and the selective Erk1/2 inhibitor PD0325901. Taken together, our findings suggest that extracellular ATP binding to P2Y1 receptors protected against glutamate-induced excitotoxicity via Erk1/2-mediated autophagy inhibition, implying the promising potential of ATP for the treatment of neurodegenerative disorders.